“Choose change”: design and methods of an acceptance and commitment therapy effectiveness trial for transdiagnostic treatment-resistant patients - Jeanette Villanueva (BMC Psychiatry, 2019)
Abstract Background Acceptance and Commitment Therapy (ACT) has been successfully established in hundreds of efficacy trials. It is less understood, however, how ACT works in real-world settings. Furthermore, little is known about how contextual variables such as treatment setting (inpatient vs. outpatient), social network and environment of the patient impact outcome. Methods This paper describes the methods of the Choose Change study that compares transdiagnostic inpatients (n = 85) and outpatients (n = 85) with varying degrees of treatment experience and treatment success (i.e., no previous treatment vs. previous remission vs. treatment-resistant). Patients received ACT during an intensive treatment phase lasting approximately twelve treatment sessions, and were accompanied up to twelve months following intensive treatment. Main outcomes include symptoms, functioning, and well-being. Multiple levels of data are investigated, including treatment context, weekly assessments, a behavioral approach test, multiple follow-up phases, and ambulatory assessment using Event Sampling Methodology, to examine patients’ daily context. Discussion We aim to investigate antecedents, consequences, and inherent processes that contribute to the maintenance or fluctuations of psychological disorders and the efficacy of ACT treatment. Furthermore, this study intends to increase understanding of how accurately participants can report on their own experiences, in order to expand our knowledge of how to probe for such information in the future. The results of Choose Change will provide basic clinical theory and clinical care with important and meaningful insights into the effectiveness of ACT, trans diagnostically, in in- and outpatients, and in a naturalistic setting. Trial registration This study was retrospectively registered in the ISRCTN Registry (registration number ISRCTN11209732) on May 20th 2016.